Differences in the immunoglobulin gene repertoires of IgG versus IgA multiple myeloma allude to distinct immunopathogenetic trajectories - Gkoliou, Glykeria; Agathangelidis, Andreas; Karakatsoulis, Georgos; Lalayanni, Chrysavgi; Papalexandri, Apostolia; Medina, Alejandro; Genuardi, Elisa; Chlichlia, Katerina; Hatjiharissi, Evdoxia; Papaioannou, Maria; Terpos, Evangelos; Jimenez, Cristina; et al. (Frontiers in Oncology, 2023)
The analysis of the immunogenetic background of multiple myeloma (MM) has proven key to understanding disease ontogeny. However, limited information is available regarding the the immunoglobulin (IG) gene repertoire in MM cases carrying different heavy chain isotypes. Here, we studied the IG gene repertoire in a series of 523 MM patients, of whom 165 and 358 belonged to the IgA and IgG MM groups, respectively. IGHV3 subgroup genes predominated in both groups. However, at the individual gene level, significant (p<0.05) differences were identified regarding IGHV3-21 (frequent in IgG MM) and IGHV5-51 (frequent in IgA MM). Moreover, biased pairings were identified between certain IGHV genes and IGHD genes in IgA versus IgG MM. Turning to the imprints of somatic hypermutation (SHM), the bulk of rearrangements (IgA: 90.9%, IgG: 87.4%) were heavily mutated [exhibiting an IGHV germline identity (GI) <95%]. SHM topology analysis disclosed distinct patterns in IgA MM versus IgG MM cases expressing B cell receptor IG encoded by the same IGHV gene: the most pronounced examples concerned the IGHV3-23, IGHV3-30 and IGHV3-9 genes. Furthermore, differential SHM targeting was also identified between IgA MM versus IgG MM, particularly in cases utilizing certain IGHV genes, alluding to functional selection. Altogether, our detailed immunogenetic evaluation in the largest to-date series of IgA and IgG MM patients reveals certain distinct features in the IGH gene repertoires and SHM. These findings suggest distinct immune trajectories for IgA versus IgG MM, further underlining the role of external drive in the natural history of MM.